The Use of Problem Based Learning Learning Models to Improve Critical Thinking Skills and Engagement and Student Learning Outcomes - Zakiyah Darajat; Suciati Suciati; Amalia Sapriati (Edumaspul: Jurnal Pendidikan, 2023)
Problem Based Learning (PBL) is a guidance method that focuses on students using objective methods, dismantling interesting problems using cooperative and collaborative learning resources and teachers as providers. Critical thinking is thinking that has characteristics. Student engagement is student participation in learning activities. Learning outcomes show the ability of students to capture, understand the subject matter given by the teacher. It is hoped that PBL can improve critical thinking skills, student involvement and student learning outcomes. The aims of this study were: (1) to determine the effect of the PBL model on students' critical thinking skills (2) to determine the effect of the PBL model on student engagement; and (3) to determine the effect of the PBL model on the learning outcomes of state elementary school students in Pamulang District. This research was conducted with a survey approach. Testing was carried out using SPSS 22.0. The sample of this research was 60 students consisting of 30 control class students and 30 experimental class students using random sampling method. Based on the results of the Sig test for the effect of PBL on critical thinking skills, the value of t count is 9.591 > t table 2.001, meaning that the application of the PBL model has an effect on critical thinking skills. The Sig test results for the effect of X is 0.000 <0.005 and the t-value is 13.443 > t-table 2.001 meaning that the application of the PBL model has an effect on critical thinking skills. The N-Gain test results for the experimental class (PBL model) were 56.424 or 56.4% which were included in the moderately effective category. With a minimum NGain score of 20% and a maximum of 74.42%. Meanwhile the NGain Score for the Control class (Conventional method) was 33.855 or 33.8% included in the ineffective category. With a minimum NGain Score of 6.30% and a maximum of 62.5%. The use of the PBL model is quite effective in improving the learning outcomes of fifth grade students of public elementary schools in Pamulang sub-district.